Growth, Investment, and Savings in the Arab Economies - Bisat, Amer (IMF Working Papers; Working Paper, 1997)
Sustaining a high rate of economic growth is the major policy issue facing the Arab economies. A detailed analysis of growth, investment, and savings for the period 1971-96, including through a growth accounting exercise, shows that increasing long-run growth requires improvements in both investment and domestic savings. In the past, the Arab region's growth was overly reliant on volatile external sources of funding, and total factor productivity growth was too low. The paper discusses the policy priorities to overcome the legacy of poor growth.